Primary Renal Ewing’s Sarcoma/Primitive Neuroectodermal Tumors: Case Series of a Rare Entity and Review of Literature - Parameswaran, Prashanth; Vallathol, Dilip Harindran; Sandhya, Saroja; NTK, Thanseer; Warrier, Narayanankutty (http://dharmais.co.id/, 2026)
Introduction: Primary renal Ewing’s sarcoma/ Primitive neuroectodermal tumor (EWS/PNET) is extremely rare. The previous literature on these is limited to case reports and series. This case series aims to bring out a rather rare entity of renal Ewing’s sarcoma, which was diagnosed at an earlier stage than previously described in the literature. Case Presentations: We hereby report a series of 3 cases of renal EWS/PNET that we encountered at our institute and had different clinical characteristics and outcomes compared to previously reported data. The treatment given was in line with that of Ewing’s sarcoma occurring at other sites. One of our cases was an elderly individual, while the other two were from younger age groups. Ewing’s sarcoma usually has a better prognosis when compared to other sarcomas affecting the skeletal/soft tissue system. But the prognosis of extra-skeletal EWS is usually intermediate when compared to skeletal Ewing’s sarcoma, as many are diagnosed at an advanced stage. In contrast, our cases were diagnosed at an earlier stage. The diagnosis is usually made through biopsy, and staging is with a positron emission tomography scan. The treatment paradigms include intensive systemic chemotherapy and definitive therapy, which may include surgery, radiotherapy, or both. One patient of ours expired due to disease progression, and the other is doing well on follow-up. The third patient was lost to follow-up after initial investigations.Conclusion: The diagnosis is typically based on histology, immunohistochemistry, and the identification of specific molecular translocation. Potent treatment regimens are urgently needed to improve prognosis in this group of patients.